2012
DOI: 10.1061/(asce)gt.1943-5606.0000546
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Method for Analysis and Design of Slope Stabilizing Piles

Abstract: Piles are extensively used as a means of slope stabilization. Despite the rapid advances in computing and software power, the design of such piles may still include a high degree of conservatism, stemming from the use of simplified, easy-to-apply methodologies. This paper develops a hybrid method for designing slope-stabilizing piles, combining the accuracy of rigorous three-dimensional (3D) finiteelement (FE) simulation with the simplicity of widely accepted analytical techniques. It consists of two steps: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…The hybrid method for the design of slope-stabilizing piles was proposed by Kourkoulis et al in 2012. It consists of two steps; (1): an analytical estimation of the resisting force needed to stabilize the precarious slope, and (2): a numerical analysis to define the adequate pile configuration that offers the required resisting force for a desired pile head displacement.…”
Section: The Hybrid Methods For Analysis and Design Of Slope Stabilizimentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid method for the design of slope-stabilizing piles was proposed by Kourkoulis et al in 2012. It consists of two steps; (1): an analytical estimation of the resisting force needed to stabilize the precarious slope, and (2): a numerical analysis to define the adequate pile configuration that offers the required resisting force for a desired pile head displacement.…”
Section: The Hybrid Methods For Analysis and Design Of Slope Stabilizimentioning
confidence: 99%
“…For piles placed in the middle of precarious slopes, it was found that beyond a distance of 5D up-slope of the piles row, the soil displacement profile becomes almost uniform [12]. Therefore, 10D (2 times 5D) was chosen to be the length of the simplified model.…”
Section: Matec Web Of Conferencesmentioning
confidence: 99%
“…The piles are embedded in the stable soil by the length of 5D (D=pile diameter), because the zone of influence of each pile has been demonstrated not to exceed 5D and the length of the pile is restricted to 10D. Fixing pile end helps to have a pile length shorter than the length proposed by Kourkoulis [14] and diminishes stabilization costs.…”
Section: Introductionmentioning
confidence: 99%
“…Their approach presumes that the soil is soft and deforms plastically around piles. Despite its rigor, the method neglects pile flexibility, pile limited length, and soil archingphenomena that may all have a substantial effect [14]. Hassiotis et al [17] presented the friction circle method by defining new expressions for the stability number to incorporate the pile resistance in slope stability analysis using a closed form solution of the beam equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation